Teachers' nutrition knowledge as a moderator on the association of habitual physical activity and quality of life among college students - Wang, Ning; Chin, Yit Siew; Appukutty, Mahenderan (Conscientia Beam, 2024)
The study employed a longitudinal design over six months gathering data in three sessions spaced two months apart and comprising 329 students from five Chinese universities. The PLS-SEM (partial least squares structural equation modelling) method was used to analyse the data. The main goal of this study is to investigate the connection between exercise and college students' growth and well-being. This study seeks to identify reasons to provide colleges with focused therapy to enhance their students' overall performance. The findings of this research showed that physical activity improves students' general quality of life particularly their self-esteem, life satisfaction and positive and negative emotions. Nutrition education and teacher support can help students optimize the excellent impact of exercise on their general quality of life. These findings have ramifications for Chinese college campuses, emphasizing the importance of encouraging physical exercise and improving teachers' understanding of student nutrition. Colleges can support their students' quality of life by encouraging frequent exercise and offering nutrition knowledge.